Geração de tecnologia agrícola em uma instituição de ensino e pesquisa: o caso da UFLA - Carvalho, Heloisa Rosa (1995)
The economical development of Brazil in the last decades was directed to urbanization and industrialization, consisting of the increase in industrial activity compared to agriculture. Industrialization was presented as the solution to generate development. The rural sector, pointed out as responsible for the slowness of development, should modernize itself. In this way, in the mid sixties, Brazil opted for modernization of the agricultural sector by means of technological changes. However, the modernization process was not homogeneous and as such it generated inequality among products, producers and regions. In this process to modernize the Brazilian agriculture, scientific research had a fundamental role to generate innovations. Research and diffusion organizations and institutions like EMBRAPA and EMBRATER were created. Simultaneously, graduate courses in the agricultural science schools were Consolidated. However, for research to come forth it is necessary that someone be interested and forces its emergence. What is noticed is that the scientific research generated by those institutions is subordinated to economical, political and ideological interests of different forces that exist in society. In this context, the following question was raised: how has Superior Agriculture School of Lavras (ESAL), currently Federal University of Lavras (UFLA), through its researchers, responded to the demand for technological innovations, by groups of interest, to stimulate the supply of new technologies and contribute to the rural sector development? The general objetive consisted in identifying the economical, social and political variables that affect the process of generation of technology at UFLA. Specifically, it was tried to identify the groups of interest that demand UFLA's research; to evaluate the influence of these groups on the institution's perfomance in supplying generated research; and, finally, to identify the contributions from UFLA in research by products. The study was based on the model of supply and demand of a public asset, which takes in consideration both the induced innovation model and the theory of groups of interest. The data collection was done through semi-structured interviews with the professors/researchers at UFLA, selected by intentional sample, and through analysis of documents and scientific production reports of the institution. The UFLA attends three technological innovation groups of interest which have distinct demands denominated. State demand, market demand and scientific demand. It was confirmed that this institution attends more the state demand, doing research for government funded agencies (like CNPq, FINEP, CAPES and FAPEMIG). In other words, if there are funds there are researches; if there are no funds researches are not done. It was observed that the market demand is also met because there is a reasonable number of research being done for private companies, but not in an institutionalized form. The contracts are not established between the institution UFLA and private enterprises, but between a company and the professor/researcher. The Foundation of Support of Teaching, Research and Extension (FAEPE), working with UFLA, is the specialized organ in establishing such contracts. The existing research demand in society by some producers, consumers, associations, etc, is not often brought to the institution, so it has not influenced the realization of several researchs. The basic research, coming from scientific demand or from the scientific community itself has been given less and less priority due to the preference for quickly applicable research with immediate responses. By attending all these demands, the supply of innovations by the institution suffers certain influences. It was confirmed through the 'Science and Practice' magazine, edited by the university itself, and through the master courses dissertations, that domestic products (basic food, vegetables and fruits) were the most researched ones compared to export products (coffee, soybean, citrus, cotton and others). Proportionally though, export products stood out significantly in number of researchs done because while the domestic cultures are in greater number, the exportable ones concentrate themselves in a smaller group. Bean was the most researched product at UFLA, followed by coffee. Bean because of individual efforts and persistence of some professors/researchers, and coffee because of the characteristics of the region itself where the university is located. Two other facts difficult the supply of innovations by the institution: the excessive work load dedicated to teaching of some professors, and the lack of a centralized sector able to organize everything produced and being produced in terms of research at the institution. In searching for information on past research projects, it was noticed that much of them has been lost. Considering the great number of research done at the institution, of can besaid that little was generated for formal extension. In analysing the Technical Bulletins and the Technical Circulars published by the Extension Coordination (COORDEX) at UFLA, it was observed that a reduced number of studies generated works disseminated by the extension. In parallel, there is no straight connection between what was mostly researched with what was mostly disseminated through COORDEX.